2007
DOI: 10.1590/s0100-69912007000500009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da função pulmonar após colecistectomias laparoscópicas e convencionais

Abstract: TCBC-GO 3 ; Enio Chaves de Oliveira, TCBC-GO 4 RESUMO: Objetivo: Avaliar a função pulmonar pós-colecistectomias laparoscópicas e subcostais abertas. Métodos: Tratou-se de um ensaio randomizado, onde se avaliaram espirometrias pós-operatórias de dois grupos, cada qual com 15 pacientes. O grupo GL foi submetido a colecistectomia laparoscópica. O grupo GA foi submetido a colecistectomia por via subcostal, por meio de mini-laparotomia e abreviado tempo anestésico-cirúrgico. As variáveis dos dois grupos foram compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…The decreased respiratory function found in this study was similar to what reported by some authors in this same type of surgery. ( 5 , 16 19 ) Gastaldi et al ( 20 ) showed lower values on the second postoperative day (FVC and FEV 1 ). Muehling et al ( 21 ) observed that a shortened fasting time in lung operations led to lower pulmonary complication rates.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The decreased respiratory function found in this study was similar to what reported by some authors in this same type of surgery. ( 5 , 16 19 ) Gastaldi et al ( 20 ) showed lower values on the second postoperative day (FVC and FEV 1 ). Muehling et al ( 21 ) observed that a shortened fasting time in lung operations led to lower pulmonary complication rates.…”
Section: Discussionmentioning
confidence: 94%
“…However, when compared with data from literature, their return to preoperative values was quicker in laparoscopic surgery than in open abdominal surgery. ( 16 , 18 , 19 )…”
Section: Discussionmentioning
confidence: 99%
“…These findings were relevant since the pulmonary mechanics were directly changed due to intubation, the general anesthetic procedure, immobility, the use of neuromuscular blocks and invasive mechanical ventilation. Moreover, the surgical incision and the presence of pain are factors present in upper abdominal surgery [2,[37][38][39], having diaphragmatic dysfunction being considered the main cause of pulmonary compromise [40,41], and these factors Inspiratory loading exercises on respiratory muscle function in post-operative gastroplasty patients could explain the findings in the control group, in which the values of all studied variables dropped.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios resaltan en relación a la respiración que es común algún nivel de limitación en la ventilación pulmonar en cirugías de Laparotomías y colecistectomías considerándose factores inherentes al acto quirúrgico como cuadro doloroso, disfunción diafragmática, extensión de la incisión y la proximidad con el aparato respiratorio, tiempo de cirugía y tipo de anestesia, que pueden resultar en problemas respiratorios restrictivos (9,10) .…”
Section: Discussionunclassified